Mineral nutrition of ornamental plants XI: deficiencies of macronutrients and boron in Catharanthus roseus (L.) G. Don and Catharanthus roseus f. albus (Sweet) G. Don - Demattê, M.E.S.P.; Haag, H.P.; Vasques, L.H. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
Plants of two botanical forms of Catharanthus roseus, with pink and white flowers, were cultived in nutrient solutions, complete or lacking one of the following elements: N, P, K, Ca, Mg, S and B. Clear deficiency symptoms were observed for all the elements and they were comproved by chemical analysis of leaves. Chemical composition of leaf matter of normal and deficient pink flowered plants were, respectively, for each of the studied elements: N(%): 3.53-1.20; P(%): 0.35-0.11; K(%)2.45-0.76; Ca(%): 1.77-0.81; Mg(%): 0.55-0.46; S(%): 0.21-0.12; B(ppm): 382-37. For plants with white flowers, these values were: N(%): 3.78-0,92; P(%): 0.38-0.09; K(%): 2.60-0.86; Ca(%): 1.37-1.15; Mg (%): 0.56-0.44; S(%): 0.10-0.07; B(ppm): 372-39.